A model for optimization of process integration investments under uncertainty - Svensson, Elin; Strömberg, Ann-Brith; Patriksson, Michael (Energy (Oxford), 2011)
The long-term economic outcome of energy-related industrial investment projects is difficult to evaluate because of uncertain energy market conditions. In this article, a general, multistage, stochastic programming model for the optimization of investments in process integration and industrial energy technologies is proposed. The problem is formulated as a mixed-binary linear programming model where uncertainties are modelled using a scenario-based approach. The objective is to maximize the expected net present value of the investments which enables heat savings and decreased energy imports or increased energy exports at an industrial plant. The proposed modelling approach enables a long-term planning of industrial, energy-related investments through the simultaneous optimization of immediate and later decisions. The stochastic programming approach is also suitable for modelling what is possibly complex process integration constraints. The general model formulation presented here is a suitable basis for more specialized case studies dealing with optimization of investments in energy efficiency. ► Stochastic programming approach to long-term planning of process integration investments. ► Extensive mathematical model formulation. ► Multi-stage investment decisions and scenario-based modelling of uncertain energy prices. ► Results illustrate how investments made now affect later investment and operation opportunities. ► Approach for evaluation of robustness with respect to variations in probability distribution.